Kriminogen dalam Hubungannya dengan Tindak Pidana Pencurian yang Berujung Pembunuhan berdasarkan Putusan PN Denpasar Nomor 619/PID.B/2025/PN Dps - Ni Ketut Sephira Gracia; I Putu Edi Rusmana; I Made Wirya Darma (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study examines the criminogenic factors that influence theft offenses leading to murder and analyzes the criminal liability of the offender based on Decision of the Denpasar District Court Number 619/Pid.B/2025/PN Dps. The research focuses on the escalation of theft into violent crime resulting in loss of life, which reflects the complex interaction between individual and environmental factors in criminal behavior. This research aims to identify the criminogenic factors underlying the crime and to evaluate their relation to criminal responsibility under Indonesian criminal law. The study employs normative legal research using statutory, case, conceptual, and analytical approaches. Legal materials were collected through library research and analyzed descriptively and qualitatively. The findings show that economic pressure, unstable psychological conditions, and situational circumstances significantly contributed to the offender’s actions. Although the offender initially intended to commit theft, the situation developed into fatal violence during the commission of the crime. Nevertheless, the offender remains criminally liable because the element of fault is fulfilled under criminal law. Criminogenic factors may be considered by judges in sentencing, but they do not eliminate criminal responsibility.